The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1097/hjh.0b013e328349666d
|View full text |Cite
|
Sign up to set email alerts
|

No effect of ultraviolet radiation on blood pressure and other cardiovascular risk factors

Abstract: Exposure to ultraviolet B did not lower blood pressure. Our results suggest that if vitamin D protects against cardiovascular disease, it involves some mechanism other than blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 43 publications
0
32
0
1
Order By: Relevance
“…Scragg et al [37,39] reported no effect of vitamin D supplementation on blood pressure [37] and no effect of ultraviolet radiation on blood pressure [39]. Jorde et al [36] observed no effect of supplementation on blood pressure in overweight subjects except for a slight increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scragg et al [37,39] reported no effect of vitamin D supplementation on blood pressure [37] and no effect of ultraviolet radiation on blood pressure [39]. Jorde et al [36] observed no effect of supplementation on blood pressure in overweight subjects except for a slight increase.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized controlled trials (RCTs) of the effect of vitamin D supplementation or UV radiation (to improve the vitamin D status) on the lipid profile [17,22,36,37] and blood pressure [36,37,38,39,40] have been divergent. Two meta-analyses of vitamin D supplementation found weak evidence to support a small effect of vitamin D on blood pressure [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…For systolic blood pressure the difference between the highest and lowest vitamin D quintile was on the borderline of statistical significance (P ¼ 0.045). In a randomized clinical trial, Scragg et al 39 found no evidence whatsoever that a UVB-induced rise in plasma 25-(OH) D levels had any effect on arterial blood pressure in a group of normotensive men and women. It must also be noted that in none of the major studies suggesting that low 25-(OH)D is related to hypertension had data been adjusted for a potent confounder, i.e., dietary calcium intake, which can lower diastolic blood pressure in healthy adults, but has much greater effects on systolic blood pressure in patients with mild to moderate hypertension.…”
Section: Multiple Sclerosismentioning
confidence: 98%
“…63,104 However, a lasting effect was not observed beyond the window of treatment. 63,101,103 These anti-hypertensive effects of UVA radiation were independent of a change in vitamin D status, and instead may have been dependent on the release of nitric oxide from preformed skin stores. 63 Some protective effects of UVB on signs of type-2 diabetes have been reported.…”
Section: 5mentioning
confidence: 99%
“…93 Indeed, whole body exposure to UVB radiation lowered blood pressure in hypertensive subjects by ~5 mmHg, 101,102 but had no effect in normotensive adults. 102,103 Acute exposure to sub-erythemal UVA radiation lowered blood pressure in healthy (normotensive) young adults. 63,104 However, a lasting effect was not observed beyond the window of treatment.…”
Section: 5mentioning
confidence: 99%